Nano Particles Dispersed Liquid Crystal Composites - Sharma, Deepika (My University, 2008)
Nano particles dispersed ferroelectric liquid crystals are playing very vital role in the development of new materials for improving display devices in industries. Nano particles dispersed ferroelectric liquid crystals have high dielectric constant, fast switching response, and large electro-optic coefficient, making them ideal for memories, capacitors and display devices etc. In this work, an attempt has been made to understand the influence of nano particles of carbon and barium ferrite on dielectric and morphological properties of FLC and how the level (wt/wt%) of nano particles concentration effect the switching response and transition temperature of FLCs. Introduction to the fundamentals of ferroelectric liquid crystals and effect of nano particles on properties of FLC has been reviewed.
M.Tech (Mat. Sc.)
Keywords: CNT; Ferroelectrics